De novo transcriptome assembly and analyses of gene expression during photomorphogenesis in diploid wheat Triticum monococcum - Fox, Samuel E.; Geniza, Matthew; Hanumappa, Mamatha; Naithani, Sushma; Sullivan, Chris; Preece, Justin; Tiwari, Vijay K.; Elser, Justin; Leonard, Jeffrey M.; Sage, Abigail; Gresham, Cathy; Kerhornou, Arnaud; et al. (My University, 2014)
Background: Triticum monococcum (2n) is a close ancestor of T. urartu, the A-genome progenitor of cultivated hexaploid wheat, and is therefore a useful model for the study of components regulating photomorphogenesis in diploid wheat. In order to develop genetic and genomic resources for such a study, we constructed genome-wide transcriptomes of two Triticum monococcum subspecies, the wild winter wheat T. monococcum ssp. aegilopoides (accession G3116) and the domesticated spring wheat T. monococcum ssp. monococcum (accession DV92) by generating de novo assemblies of RNA-Seq data derived from both etiolated and green seedlings. Principal Findings: The de novo transcriptome assemblies of DV92 and G3116 represent 120,911 and 117,969 transcripts, respectively. We successfully mapped ~90% of these transcripts from each accession to barley and ~95% of the transcripts to T. urartu genomes. However, only ~77% transcripts mapped to the annotated barley genes and ~85% transcripts mapped to the annotated T. urartu genes. Differential gene expression analyses revealed 22% more light up-regulated and 35% more light down-regulated transcripts in the G3116 transcriptome compared to DV92. The DV92 and G3116 mRNA sequence reads aligned against the reference barley genome led to the identification of ~500,000 single nucleotide polymorphism (SNP) and ~22,000 simple sequence repeat (SSR) sites. Conclusions: De novo transcriptome assemblies of two accessions of the diploid wheat T. monococcum provide new empirical transcriptome references for improving Triticeae genome annotations, and insights into transcriptional programming during photomorphogenesis. The SNP and SSR sites identified in our analysis provide additional resources for the development of molecular markers.
Citation: Fox, S., Geniza, M., Hanumappa, M., . . . Jaiswal, P. (2014). De Novo Transcriptome Assembly and Analyses of Gene Expression during Photomorphogenesis in Diploid Wheat Triticum monococcum. PLoS One, 9(5), e96855. https://doi.org/10.1371/journal.pone.0096855
Keywords: Triticum monococcum (2n); Wheat; Diploid wheat; De novo transcriptome assemblies